GM-free private standards, public regulation of GM products and mass media - Mauro Vigani; Alessandro Olper (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
This paper provides evidence on private standards on genetically modified (GM) organisms for 44 retailers operating in 54 countries, distinguishing between retailers not using GM ingredients, and retailers using ingredients which are potentially GM in private label products. Using this information, we empirically investigate the drivers that induce retailers to adopting a GM-free private standard. The results show that many of the drivers highlighted in the literature, such as historical factors, communication infrastructure and sectoral conditions affect the likelihood of adopting a private standard. Moreover, we tested additional hypotheses from the political economy of standard formation and of mass media. Key results show that a higher share of public media reduces the probability of adopting GM-free private standards, while a higher heterogeneity in the GMO public standards increase this probability.
Keywords: D72; Q13; Q16; Q18; 330; GM-free private standards; vertical differentiation; political economics; media market; Biotechnisches Produkt; Handelskette; Produktdifferenzierung; Öffentliche Meinung